Efficacy of contralateral acupuncture in women with migraine without aura: protocol for a randomised controlled trial - Ling Zhao; Qifu Li; Yanan Wang; Jialei Feng; Xinghe Zhang; Siwen Zhao; Chonghui Xing; Yongli Song; Xuanxiang Zeng; Meng Kong; Yunqiu Zheng; Taipin Guo (BMJ Open)
Introduction Migraine is a common neurological disorder with a higher prevalence occurring in women. Migraine without aura (MwoA) is the most common type of migraine. In recent years, the safety and effectiveness of acupuncture for migraines have been internationally recognised. Contralateral acupuncture (CAT) (Jùcì) is an ancient classic acupuncture technique from Huang Di Nei Jing that refers to the acupoints on the right side (healthy side) selected for diseases on the left (affected side) and vice versa. Some studies have shown that efficacy of CAT on the painful disorder is even better than ipsilateral acupuncture (IAT), but there remains a lack of high-quality evidence to support it.Methods and analysis This is a single-centre, randomised and sham-controlled clinical trial in China with three parallel groups that aim to evaluate the efficacy of CAT in women with unilateral MwoA. 243 participants will be randomly divided into the experimental group (CAT group), control group 1 (IAT group) and control group 2 (sham acupuncture group) (1:1:1 allocation ratio). Each group will be given 30-minute treatment sessions, once every other day, approximately three times per week, for a total of 24 treatments and follow-up visits two times. The primary outcome is the changes in days of migraine attacks. The secondary outcomes are frequency of migraine attacks, intensity of migraine, migraine duration, the dose of intake of acute medication, the Migraine-Specific Quality of Life Questionnaire, the Migraine Disability Assessment Score, the Headache Impact Test-6 and the Pittsburgh Sleep Quality Index. The data will be collected at the baseline time (week 0), end of treatment (week 4–8) and the follow-up time (week 12–16). Adverse events will be collected and recorded during each treatment.Ethics and dissemination Ethics approval was obtained from the Ethics Committee of the Sports Trauma Specialist Hospital of Yunnan Province (2021-01). All participants will provide written informed consent before randomisation. The results of this study will be published in a peer-reviewed journal and presented at conferences.Trial registration number Chinese Clinical Trial Registration Center (ChiCTR2100051479).